APLIKASI HEALTH BELIEF MODEL PADA PERILAKU PENCEGAHAN DEMAM BERDARAH DENGUE - Helmy Bachtiar Attamimy; M. Bagus Qomaruddin (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2017)
Dengue fever is an acute fever disease that caused by dengue virus by the bite of mosquito of the genus aedes. In Indonesia, large number of dengue fever was fluctuatited every year, including East Java. One of large number cases is the Kediri. The effort of dengue fever preventions should have been comprehensive, including behavio factorsr. The aim know the relationship between the trust factor through effort of dengue fever preventions in the working area of Community Health Center Sukorame, Mojoroto, Kediri. This research uses quantitative approach that shaped descriptive analytic by correlation study and cross sectional design. An instrument that is used was interview by the simple random sampling technique. The data conducted in research is respondents as many as 100 people in the workplace of Community Health Center Sukorame. The dengue fever preventions effort as variable dependent, and the trust of perceived susceptibility, severity, cues to action, benefits, and bariers as independent variables. The result show that relation between dengue fever prevention effort and perceived susceptibility rs= 0,292, saverity rs= 0,406, cues to actions rs= 0,432, benefits rs= 0,239, and barriers rs= -0,122. Beside that, among independent variable factors, perceived barriers is not significant by sign = 0,144. Conclusion of the research that there is relation between the trust factor on perceived severity, susceptibility, cues to action and benefits for dengue fever prevention in the working area of Community Health Center Sukorame, Mojoroto, Kediri, and perceived barriers which aren’t in related with dengue fever prevention in that areas.Keyword: belief factor, HBM, dengue fever prevention behavior